Characteristics of Atopic Dermatitis Patients Treated with Crisaborole: Real-World Data from a Large Healthcare Provider Database in Israel - Weil C; Adiri R; Chodick G; Gersten M; Cohen Barak E (Dove Medical Press, 2022)
Clara Weil,1,* Roni Adiri,2,* Gabriel Chodick,1,3 Merril Gersten,2 Eran Cohen Barak4,5 1Maccabitech Institute for Research and Innovation, Maccabi Healthcare Services, Tel Aviv, Israel; 2Pfizer Israel, Herzliya Pituah, Israel; 3Faculty of Medicine, Tel Aviv University, Tel Aviv, Israel; 4Dermatology Department, Emek Medical Center, Afula, Israel; 5Bruce and Ruth Rappaport Faculty of Medicine, Technion, Haifa, Israel*These authors contributed equally to this workCorrespondence: Gabriel Chodick, Maccabitech Institute for Research and Innovation, Maccabi Healthcare, Keufmann 4 St, Tel Aviv, 68125, Israel, Tel +972-514-3755, Email hodik_g@mac.org.ilBackground: In recent years, new treatments dedicated to atopic dermatitis (AD) have become available in Israel, including crisaborole, a small molecule with unique benzoxaborole chemistry.Objective: To describe baseline characteristics, history of AD therapies, and use of health-care services of early crisaborole users in real-world settings.Methods: A retrospective cohort study was performed using the data of a large health provider in Israel. AD patients treated with crisaborole since it became commercially available in Israel in July 2019 through end of Sep 2020, were included. Baseline demographics and clinical characteristics, prior AD-related treatments and healthcare resource utilization were collected.Results: A total of 441 patients were included (57.8% females, median age = 21.1y; interquartile range = 10.5- 40.8). In 62.1%, a dermatologist prescribed the first dispensed crisaborole. Median time from AD diagnosis to crisaborole treatment was 6.6 years. Up to 12 months prior to crisaborole treatment, low-, mid- and high-potency TCS were used by 30.8%, 31.1% and 55.8% of patients, respectively. Treatments related to moderate-to-severe AD were dispensed to 38.5% of patients in the prior 5 years. Asthma and allergic rhinitis were documented among 22.2% and 37.2%, respectively. In the past year, patients had a median of 9 visits to primary care physicians, 84.6% visited a dermatologist (≥ 5 visits: 12.9%).Conclusion: While crisaborole is indicated for mild-to-moderate disease, results suggest that a significant proportion of patients had history of advanced AD therapies suggestive of moderate-to-severe AD.Keywords: atopic dermatitis, topical calcineurin inhibitors, real-world data